Pelatihan Identifikasi Cepat Fitokimia pada Mahasiswa STIFI BP Palembang - Ferdian, Arif; Arifa, Nurwahidatul; Bakhtiar, Amri (Yayasan Literasi Sains Indonesia, 2023)
Identification of phytochemicals is an important preliminary test that pharmacy students need to know and understand. As is known, that natural ingredients are an important aspect that plays a role in herbal medicine. One of the most prominent uses of plants is as a medicinal ingredient. In determining the traditional use of natural materials, it is necessary to know which groups of chemical compounds are contained in natural materials. Chemical compounds contained in natural products are grouped into alkaloids, phenolics, flavonoids, saponins, steroids and terpenoids. To determine the class of compounds in natural products, it is necessary to carry out preliminary tests quickly, namely by testing phytochemicals. Phytochemical identification training is aimed at STIFI Bhakti Pertiwi Palembang students who conduct field studies at Anai Land, Padang Pariaman Regency, Padang, West Sumatra. This field study activity is held as a support for natural product chemistry lectures. Phytochemical testing was carried out in groups guided by each. Students who have received training can carry out phytochemical testing of natural ingredients as a provision for final project research.